Correlation of knowledge with the behavior of the application of the protocol health during a pandemic covid-19 ( case studies in traders dawet jabung ) - Ramadhanintyas, Karina Nur; Amelia, Permata; Kuswanto, Kuswanto (Universitas Respati Yogyakarta, 2021)
Corona virus disease 2019 ( covid-19 ) caused by sars-cov2 now spread throughout the world, including Indonesia. Health protocol are advised to reduce the risk of disasters, as the spreading and death caused by covid-19. Community awareness health policy of the application of the protocol is very effective in reducing the spread of the virus. The purpose of this research want to know the knowledge with the manners the protocol for pandemic covid-19 health. In this research, researchers use descriptive quantitative research. Research methodology used is analytic of survey research is the cross sectional. In analyzing data, use the researchers chi-square. Population as many as 40 respondents and 37 samples from respondents. The results of the bivariat showed there was free of the relations between variables that knowledge with the behavior of the health protocol ( p-value = 0,006 ). In this research, the study analyzed that most influential chi-square variables, which is knowledge. Respondents who know better are critical to someone to behave well in implementing health protocol. Conclusions in this research is that there a significant correlation exists between knowledge by behavior in carrying out health protocol. Hopefully the traders dawet jabung can apply the health protocol 3M.